Effectiveness of dark chocolate in reducing dysmenorrhea pain intensity in adolescent girls: A systematic literature review - Firnandani, Sherly; Achyar, Khamidah (Alma Ata University Press, 2025)
Background: Dysmenorrhea is pain during menstruation that usually occurs in the lower abdomen, waist, and even back. According to WHO (2022), it increased to 2,398,563 people with the incidence of dysmenorrhea almost 73% of that number. The prevalence of dysmenorrhea in Indonesia is 107,673 people (64.25%), consisting of 59,671 people (54.89%) experiencing primary dysmenorrhea and 9,496 people (9.36%) experiencing secondary dysmenorrhea.Objectives: To further study “The effectiveness of Dark Chocolate on reducing the intensity of dysmenorrhea pain in adolescent girls” which hopes to help reduce the intensity of dysmenorrhea pain by utilizing herbs, one of which is dark chocolate.Methods: This type of research is a Systematic Literature Review by searching for journals using the Scopus, Pubmed, DOAJ, CORE, and Google Schoolar databases from 2019 - 2024 and the literature selection process using the PRISMA diagram with a Quasy Experimental research design. The article selection process uses the Mendeley Application.Results: Four out of 1,115 articles found that there was a decrease in dysmenorrhea pain intensity after being given a dark chocolate intervention 35gr – 95gr when pain or the beginning of menstruation.Conclusions: This Study Conclude that consuming dark chocolate can reduce dysmenorrhea pain intensity in adolescent girls.